Veillonellaceae family members uniquely alter the cervical metabolic microenvironment in a human three-dimensional epithelial model - Mary E. Salliss (Nature Portfolio, 2021)
Abstract Bacterial vaginosis (BV) is a gynecologic disorder characterized by a shift in cervicovaginal microbiota from Lactobacillus spp. dominance to a polymicrobial biofilm composed of diverse anaerobes. We utilized a well-characterized human three-dimensional cervical epithelial cell model in conjunction with untargeted metabolomics and immunoproteomics analyses to determine the immunometabolic contribution of three members of the Veillonellaceae family: Veillonella atypica, Veillonella montpellierensis and Megasphaera micronuciformis at this site. We found that Veillonella spp. infections induced significant elevation of polyamines. M. micronuciformis infections significantly increased soluble inflammatory mediators, induced moderate levels of cell cytotoxicity, and accumulation of cell membrane lipids relative to Veillonella spp. Notably, both V. atypica and V. montpellierensis infections resulted in consumption of lactate, a key metabolite linked to gynecologic and reproductive health. Collectively our approach and data provide unique insights into the specific contributions of Veillonellaceae members to the pathogenesis of BV and women’s health.